Security and cryptography for networks : 11th International Conference, SCN 2018, Amalfi, Italy, September 5-7, 2018, Proceedings /: 11th International Conference, SCN 2018, Amalfi, Italy, September 5-7, 2018, Proceedings. (2018) - Unknown
No abstract available